DISC1 Pathway in Brain Development: Exploring Therapeutic Targets for Major Psychiatric Disorders - Kamiya, Atsushi; Sedlak, Thomas W.; Pletnikov, Mikhail V. (Frontiers in Psychiatry, 2012)
Genetic risk factors for major psychiatric disorders play key roles in neurodevelopment. Thus, exploring the molecular pathways of risk genes is important not only for understanding the molecular mechanisms underlying brain development, but also to decipher how genetic disturbances affect brain maturation and functioning relevant to major mental illnesses. During the last decade, there has been significant progress in determining the mechanisms whereby risk genes impact brain development. Nonetheless, given that the majority of psychiatric disorders have etiological complexities encompassing multiple risk genes and environmental factors, the biological mechanisms of these diseases remain poorly understood. How can we move forward in our research for discovery of the biological markers and novel therapeutic targets for major mental disorders? Here we review recent progress in the neurobiology of Disrupted in schizophrenia 1 (DISC1), a major risk gene for major mental disorders, with a particular focus on its roles in cerebral cortex development. Convergent findings implicate DISC1 as part of a large, multi-step pathway implicated in various cellular processes and signal transduction. We discuss links between the DISC1 pathway and environmental factors, such as immune/inflammatory responses, which may suggest novel therapeutic targets. Existing treatments for major mental disorders are hampered by a limited number of pharmacological targets. Consequently, elucidation of the DISC1 pathway, and its association with neuropsychiatric disorders, may offer hope for novel treatment interventions.